Potential anticancer effect of sodium caprate on human gastric cancer cells. (5th August 2022) - Kim, Nam-Hee; Park, Jung Ho; Koo, Dong-Hoe; Lee, Taeheon; Yang, Jeong-Yoon; Lee, Hee-Young
The role of sodium caprate (C10 ) in enhancing drug absorption is well established; however, little information is available on its role as an anticancer drug. This study aimed to evaluate the anticancer effect of C10 in gastric cancer cells. The mechanism of cytotoxicity of C10 was evaluated by western blotting following treatment of the gastric cancer cells with various concentrations of C10 . C10 cytotoxicity was measured via MTS (3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H tetrazolium), lactate dehydrogenase (LDH), cAMP, and ATP assays. Gastric cancer cells were observed by electron microscopy following treatment with C10 . Then, xenograft mice that were inoculated with gastric cancer cells were treated with C10 for 4 weeks, after which the changes in tumor size were measured. C10 triggered apoptosis in the gastric cancer cells through the mitochondrial pathway at concentrations of more than 0.2 mM. However, 15 mM of C10 induced necrosis in gastric cancer cells by causing cellular swelling and the formation of holes in the cell membrane. Levels of cAMP and ATP decreased significantly following exposure to 15 mM C10 for 1 h. Additionally, the size of the xenograft tumors was significantly reduced by 24% after 4 weeks of C10 treatment ( p < 0.05). This study indicates that C10 induces apoptosis and necrosis in a concentration-dependent manner and has clear anticancer effects on gastric cancer cells.